PERAN GURU DALAM MENINGKATKAN LITERASI MEMBACA DAN MENULIS SISWA KELAS 4 DI MIN 2 SIDOARJO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the teacher’s role in enhancing reading and writing literacy skills among fourth-grade students at MIN 2 Sidoarjo. The research focuses on: (1) the forms of teacher roles in developing students’ literacy skills, (2) the learning barriers encountered by students, and (3) the strategies implemented by the teacher to overcome these barriers. A qualitative approach with a case study design was employed, and the data were collected through observation, interviews, and documentation. The findings reveal that the teacher acts as a facilitator, motivator, and guide in the literacy learning process. The main challenges identified include low reading interest, an unconducive learning environment, and students’ difficulties in comprehending texts. To address these issues, the teacher applied various strategies, including the use of engaging learning media, daily reading routines, and contextual, enjoyable writing activities. The study concludes that active teacher involvement supported by appropriate instructional strategies can significantly and gradually improve students’ literacy skills.